Estrategias Pedagógicas Y Su Influencia En El Desarrollo De Las Inteligencias Múltiples De Los Estudiantes De La Unidad Educativa “6 De Octubre” De La Ciudad De Ventanas - Fajardo Guedez, Nila M. (2015)
This work was carried out at the "Seis de Octubre Education Unit, Ventanas Canton, Los Rios Province. The research topic was "Teaching strategies and their influence on the development of multiple intelligences of students in the "Seis de Octubre" Educational Unit of Ventanas City", responding to the problem of the lack of variety in the delivery of knowledge to the students at the center above mentioned. For this purpose a problem tree was developed around the negative situation and the causes and were isolated possible effects that could be generated if the causes continue to be met. An extensive consultation took place in print and on the Internet, seeking as much information from experts in the field. Later surveys were applied to the teachers of "Seis de Octubre Education Unit; to respective samples of both legal representatives and students. The results showed that most teachers and are applying the curriculum too tight to student text; likewise, they pretend that their students learn in the same way as they did. It was also found that teachers do know about multiple intelligences, but lack the initiative or training needed to develop different intelligences in the process of their subjects. A solution suggested is the development of a methodological guide and a choice of activities for the development of multiple intelligences in each subject and student group.